2005
DOI: 10.1002/jcb.20539
|View full text |Cite
|
Sign up to set email alerts
|

Low pH and Helicobacter pylori increase nuclear factor kappa B binding in gastric epithelial cells: A common pathway for epithelial cell injury?

Abstract: Helicobacter pylori infection results in peptic ulceration and chronic gastritis through mechanisms which are not fully elucidated. Live H. pylori activate the pro-inflammatory transcription factor NF-kappaB in gastric epithelial cells. Patients may have peptic ulcer disease in the absence of H. pylori infection; therefore other factors contribute to the inflammatory process. Maximal acid output in patients with H. pylori infection and duodenal ulceration is significantly increased indicating a role for acid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
3
15
1
Order By: Relevance
“…The level of binding of H. heilmannii bacteria to gastric epithelial cells was higher at pH 7 than at pH 2. This is consistent with the physiological pH gradient in the stomach, ranging from pH 1 to 2 in the gastric lumen to pH 6 to 7 at the epithelial cell surface (49)(50)(51). Following this theory, we would expect better binding to human gastric mucins at pH 2, since they are located in the acidic lumen of the stomach.…”
Section: Discussionsupporting
confidence: 82%
“…The level of binding of H. heilmannii bacteria to gastric epithelial cells was higher at pH 7 than at pH 2. This is consistent with the physiological pH gradient in the stomach, ranging from pH 1 to 2 in the gastric lumen to pH 6 to 7 at the epithelial cell surface (49)(50)(51). Following this theory, we would expect better binding to human gastric mucins at pH 2, since they are located in the acidic lumen of the stomach.…”
Section: Discussionsupporting
confidence: 82%
“…Hypochlorhydria provokes superficial gastritis, which may progress to atrophic gastritis, intestinal metaplasia, dysplasia, and eventually carcinoma35. The mechanisms underlying H. pylori -mediated transient hypochorhydria are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence indicating that an acidic environment contributes to the regulation of expression of many genes during the inflammatory process. Previously, we demonstrated that acid induces NF-kB and AP-1 binding activities in gastric epithelial cells and this induction was mediated through MEK1-ERK1/2 dependent signaling pathways [O'Toole et al, 2005]. In this study, we have demonstrated that lowering the extracellular pH from 7.4 (resting pH of the medium) to pH 6.0 activates Egr-1 transcription factor in AGS cells.…”
Section: Discussionmentioning
confidence: 77%
“…Many tumors have a relatively acidic extracellular pH, although the intracellular pH of tumor cells remains normal due to the efficient maintenance of a large proton gradient across the membrane. O'Toole et al [2005] demonstrated that AGS cells exposed to acidic conditions can regulate their intracellular pH. It is known that the stomach is protected from the deleterious effect of gastric acid by several mechanisms [Bhaskar et al, 1992].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation